A SECOND OPTION IN SPECIAL SEPARATION OPERATIONS: SUPERCRITICAL FLUID PROCESSES - Dincer, Salih; Acarali, Nil Baran; Uzun, Ipar Nimet; Deniz, Sennur (YILDIZ TECHNICAL UNIV, 2007)
Processes using supercritical fluids constitute another special separation process option other than the membrane processes which have been presented in one of the previous issues as alternative to conventional separation processes. Separation processes that make use of either membranes or supercritical fluids are considered to be special because of the separation media or agents used which are much different than those used in conventional processes. As the separation or the separation with reaction takes place through a membrane made of materials such as polymers or ceramics in membrane processes, separation or separation with reaction takes place in a fluid above its critical temperature and pressure, in other words in a fluid medium under supercritical conditions in supercritical fluid processes. The fact that properties of fluids in supercritical conditions can be tuned by pressure and temperature changes rather easily enables such fluids to be quite successful and advantageous relative to conventional solvents in separation oriented applications like solid or liquid extraction (primarily in food, cosmetics, chemical and biochemical industries), purification, particle size design, pore formation, and various reactions followed by separation applications such as polymerization, modification of various oils and waste water treatment. However special separation processes are not expected to replace conventional separation processes completely, and in some applications they may even be designed to form hybrid processes with conventional processes. In this article, supercritical fluid applications as special separation processes were investigated thoroughly stressing thermodynamics, kinetics, transport phenomena, technology and economics.
Keywords: Supercritical fluid; solid or liquid extraction; food; cosmetics; reaction medium; polymerization; purification; particle size design; biotechnology; oil modification; waste water treatment; DIOXIDE PHASE-EQUILIBRIA; CARBON-DIOXIDE; DISPERSION POLYMERIZATION; METHYL-METHACRYLATE; ESSENTIAL OIL; VOLUMETRIC PROPERTIES; VEGETABLE-OILS; EXTRACTION; CHROMATOGRAPHY; BIODIESEL; Engineering